Avaliações psicofísicas cromática e acromática de homens e mulheres expostos a solventes orgânicos - Oliveira, Ana Raquel de (2015)
Workers chronically exposed to a variety of organic solvents may suffer from changes in color vision and contrast sensitivity (CS). However, few studies have investigated whether there are sex-related differences in these changes, one of the factors that can change the toxicokinetics of solvents. Hence, the aim of this study was to determine whether there would be differences between women and men exposed in terms of their chromatic and achromatic visual psychophysical responses. A total of 44 individuals, Control Group total (CGt; n = 22) and Study Group total (SGt; n = 22) participated in the experiment, subdivided into the following groups: Study Group men (SGm): 11 men exposed to solvents (Age, M = 30.18, SD = 6.48; Education level, M = 9.73, SD = 2.10; Work duration, M = 6.53, SD = 4.38); Study Group women (SGw): 11 women exposed to solvents (Age, M = 26.91, SD = 5.86; Education level, M = 10, 36, SD = 0.92; Work duration, M = 4.70, SD = 3.53); Control Group men (CGm): 11 unexposed men (Age, M = 26.73, SD = 6.5; Education level, M = 9.73; SD = 1.8); Control Group women (CGm): 11 unexposed women (Age, M = 26.55, SD = 6.5; Education level, M = 10.45; SD = 1.51). The project was approved by the Ethics Committee of the Health Sciences Center (SCC) at the Federal University of Paraíba (UFPB), with CAAE registry number 21350113.9.0000.5188. Initially the participants underwent a screening step, with the following inclusion criteria, among others: a 20/20 or corrected visual acuity (evaluated via optotypes and Rasquin testing) and no dyschromatopsia (evaluated using Ishirara Test). Assessment of color perception was performed using the D15 desaturated Lanthony test (D15d) and the Cambridge Colour Test (CCT). The evaluation was performed by CS stimulation using sinusoidal gratings with a vertical spatial frequency of 0.2, 0.5, 1.0, 2.0, 5.0, 10, and 16 cycles per degree (cpd) of visual angle. Furthermore, an assessment of body composition from an examination of bioimpedance. The data were analyzed using the SPSS software package, version 21. First, the overall results between the SGt group (n = 22) and CGt group (n = 22) were compared, and were subsequently compared by sex (n = 11). The results showed that the study group (SGt) (Mdn = 1.18; M = 1.31, SD = 0.32) had a significantly higher ICC (U = 128, p = 0.01) than the CGt (Mdn = 1.09; M = 1.10, SD = 0.26), while there were no significant differences between solvent-exposed men and women (U = 51.0, p = 0.53). In CCT testing (Trivector Protocol), the SGt had a length corresponding to the vector protan axis (Mdn = 50.00; M = 54.00, SD = 16.42), and was significantly higher (U = 133.50, p = 0, 01) than the combined CGt group (Mdn = 40.00; M = 42.59, SD = 16.42), while according to the ellipse protocol, the SGt (Mdn = 981.15; M = 8086.81 ; SD = 22787.81) had a significantly higher ellipse area in A3 (U = 158.00, p = 0.04) compared to the CGt (Mdn = 657.30; M = 781.75, SD = 528.68), but men and women showed no significant differences in both CCT protocols (p > 0,05). The results of the CS showed that the SGt had lower CS in the following frequencies: 0.2 (U = 116,500, p = 0.003); 0.5 (U = 117.00, p = 0.003); 5.0 (U = 149.50, p = 0.03) and 10 cpd (U = 150.00, p = 0.03) compared to the CGt. The SGm (U = 25.0, p = 0.02) had significantly higher CS than SGm at the 0.5 cpd frequency value. The correlational analyses showed that among SGw, the diameter values of circles equivalent to the A1 and A2 ellipse areas retained a significant correlation with MCM: ρ = -0.68; p = 0.02 and ρ = -0.83; p = 0.01, respectively. Among SGw, the diameter value of the circle equivalent to the A2 area was negatively correlated with fat mass: ρ = -0.67; p = 0.02, in other words a greater amount of fatty tissue was correlated with a lower error trend in the red-green opponency axis, in addition, the diameter value of the circle equivalent to the A3 area had a positive correlation with MCM: ρ = 0.61; p = 0.04, i.e. a greater amount of MCM was correlated with a greater tendency to error in the color opponency axis. In short, the data on color vision and the SC obtained by solvent-exposed women and men found no strong evidence of possible differences between the sexes. However, the associations of psychophysiological measurements with the body measurements seem to indicate that fat can act as a protective factor of the organism against the effects of solvents, since fatty tissues may retain a proportion of solvents. In this regard, women could be less affected by solvents by having, on average, a larger proportion of adipose tissue than men.